x*x=16+(x-4)*(x+4)

Simple and best practice solution for x*x=16+(x-4)*(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*x=16+(x-4)*(x+4) equation:


Simplifying
x * x = 16 + (x + -4)(x + 4)

Multiply x * x
x2 = 16 + (x + -4)(x + 4)

Reorder the terms:
x2 = 16 + (-4 + x)(x + 4)

Reorder the terms:
x2 = 16 + (-4 + x)(4 + x)

Multiply (-4 + x) * (4 + x)
x2 = 16 + (-4(4 + x) + x(4 + x))
x2 = 16 + ((4 * -4 + x * -4) + x(4 + x))
x2 = 16 + ((-16 + -4x) + x(4 + x))
x2 = 16 + (-16 + -4x + (4 * x + x * x))
x2 = 16 + (-16 + -4x + (4x + x2))

Combine like terms: -4x + 4x = 0
x2 = 16 + (-16 + 0 + x2)
x2 = 16 + (-16 + x2)

Combine like terms: 16 + -16 = 0
x2 = 0 + x2
x2 = x2

Add '-1x2' to each side of the equation.
x2 + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
0 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| P/g=10 | | 9x-5-6x-2=6x-1 | | -10-9z+10z=-12 | | 5g+2=10-3g-8 | | -5r+5=-6r+2 | | (3x-1)(6x+9)=0 | | (x-4)*(x+4)=486 | | 3.50t+5.50+6t=51 | | d+6=10-3d | | 1-7n-1=-8n | | (x-4)*(x-4)=486 | | 60+60+x-20=360 | | 9x-5-6x-2=6x-7 | | -4n+6n=6n-12 | | 2q-6=3+3q | | 60+60+x-20=90 | | 2(x-2)(x-6)=0 | | 17/3x1/3 | | -x-2=12+x | | 60+60+x-20=180 | | 2g=g+10 | | 12/2q=36 | | 3y=x+8.5 | | 5=x-3(x+2) | | P(-2)=x^4-4x^3-7x^2+22x+18 | | 11n^2-24n+4=0 | | 8x3/24 | | 30-3y-6x=0 | | 7x+5=x+7 | | -5-3v=11-5v | | 30x-3x-6y=0 | | b=4300e-0.02(5) |

Equations solver categories